Quadrature Acoustic Frequency Combs Multiplexing for Massive Parallel Underwater Acoustic Communications. Issue 2 (23rd December 2021) - Qian, Zhiwen; Sun, Wanzhong; Ma, Xinyu; Han, Guangyao; Fu, Xiaomei; Zhai, Jingsheng
Abstract: Underwater acoustic (UWA) communication has been developing rapidly over the past decades for its crucial position in resource exploration, environmental monitoring, and scientific research. However, the transmission data rate of UWA communication is limited by the narrow bandwidth of the underwater acoustic channel. Here, the generation of quadrature acoustic frequency combs (AFCs) is first reported. Massive parallel channels achieved with multiplexing of AFCs for UWA communication are demonstrated. The generated AFCs have unique characteristics which have a stable and precise division in frequency and time domain simultaneously with carrier spacing of 1 Hz with the stability of 10 −8 . The different frequency spacing in combs leads to different teeth spacings in time, which is orthogonal and separable in the time domain. The orthogonality among AFCs provides a new dimension for multiplexing and can drastically increase channel efficiency. The underwater acoustic communication experiments demonstrate that it is drastically increasing the transmission rate to 45.33 kb s −1 and high spectral efficiency of 1.51 (channel s −1 ) Hz −1 without utilizing other modulation techniques by a single transducer. Since AFCs multiplexing is a completely independent degree of freedom that can be readily integrated with other high order modulation techniques, such as quadrature amplitude modulation and phase‐shift keying, in a single channel, AFCs multiplexing opens a new dimension for acoustic communication. Abstract : Underwater acoustic communication is of fundamental importance for marine science and technology. In this work, the generation of quadrature acoustic frequency combs (AFCs) is first reported. Massive parallel channels achieved with multiplexing of AFCs for UWA communication are demonstrated that it is drastically increasing the transmission rate to 45.33 kb s −1 and high spectral efficiency of 1.51 (channel s −1 ) Hz −1 .